2000
DOI: 10.1515/cclm.2000.027
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of Patients with Acute Chest Pain

Abstract: The enzyme activities of creatine kinase (CK), its isoenzyme MB (CK-MB) and of lactate dehydrogenase isoenzyme 1 (LD-1) have been used for years in diagnosing patients with chest pain in order to differentiate patients with acute myocardial infarction (AMI) from non-AMI patients. These methods are easy to perform as automated analyses, but they are not specific for cardiac muscle damage. During the early 90's the situation changed. First creatine kinase MB mass (CK-MB mass) replaced the measurement of CK-MB ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
3
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 92 publications
0
34
3
4
Order By: Relevance
“…Similarly, it has been shown that serial troponin measurement is equivalent to measurement of CK-MB for detection of reinfarction (29 ). Measurement of CK-MB by activity measurement is clinically and methodologically inadequate (30,31 ) and is not recommended (2 ) but was cited as performed on cost grounds and clinician familiarity. In sum, there is no longer justification for CK-MB activity or mass measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that serial troponin measurement is equivalent to measurement of CK-MB for detection of reinfarction (29 ). Measurement of CK-MB by activity measurement is clinically and methodologically inadequate (30,31 ) and is not recommended (2 ) but was cited as performed on cost grounds and clinician familiarity. In sum, there is no longer justification for CK-MB activity or mass measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation blood samples were drawn immediately before and 5 min after the end of the HD session. Therefore, due to the specific release pattern of troponin following myocardial injury (HD lasted less than 4 hr and troponin concentrations in blood increase only from 4 to 6 hr after onset of chest pain) (43), the changes observed could be most conceivably attributed to HD. At variance with previous investigations that used the lower limit of the analytical sensibility of the assay, we applied a more reliable diagnostic threshold, corresponding to the lowest cTnT concentration associated with a 10% total imprecision (33).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, cTnI will undergo multiple biological transformations (phosphorylation, oxidation or proteolysis) that could induce smaller molecules, possibly eliminated by the kidney [21]. Moreover, cTnI molecular weight is around 24 kDa, allowing this molecule to be theoretically filtered by kidney glomerules [22]. Thus, we may hypothesize that during chronic kidney disease, alteration in the integrity of the filtration barrier could be responsible for a defect in renal clearance leading to the accumulation of cTnI or its degradation products.…”
Section: Discussionmentioning
confidence: 99%